Application of reverse transcriptase nested, hemi-nested And multiplex polymerase chain reaction techniques For the detection of pv 11, pv 3462 and cvs Strains of rabies virus - THANGARAJ SEKAR; GANESAN CHANDRA MOHAN; BALA SUBRAMANIAN KARTHICK; ANANDA ARONE PREMKUMAR; BHEEMAN SUNDARAN; BALARAMAN SEKAR (International Journal of Pharma and Bio Sciences, 2018)
Rabies viral strains PV11, PV 3462 and CVS were propagated in Vero cell line, Neuroblastoma cell (in-vitro) and mouse brain (in-vivo) respectively. The RNA extracted from these strains were converted to cDNA. The cDNA from PV 11, PV 3462 and CVS strains of rabies virus were used as sample for the standardization of Nested PCR, Hemi-Nested PCR and Multiplex PCR techniques. Rabies virus specific primers for LP1, LP2, MP, NP and PP genes were designed, synthesized and optimum condition for each set of primers were standardized using gradient PCR. Nested PCR was standardized with primer pairs of LP1 for primary amplification followed by LP2 for secondary amplification. Hemi – nested PCR using LP1 primer for primary amplification and secondary amplification using forward primer of LP2 and reverse primer of the LP1 was carried out. The multiplex PCR was standardized using LP1 & PP, MP&NP gene specific primers since they had similar amplification conditions as optimized by gradient PCR analysis. The genes of three different strains got amplified with the same product length with their respective primers and also three strains were detected using Nested, Hemi-Nested and Multiplex PCR techniques. The Fluorescent Antibody Technique detected only the live virus particle present in the sample whereas the present PCR technique detected the rabies virus even in its inactivated state.